Nur Sabihah Apriliyani Pengaruh Pengungkapan Corporate Social Responbility (CSR), Ukuran Perusahaan, dan Leverage terhadap Kinerja Keuangan pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Periode 2019-2023 - Apriliyani, Nur Sabihah; Riswan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the influence of corporate social responsibility (CSR), company size, and leverage on financial performance in manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The research method used is quantitative by utilizing secondary data. Sample selection was carried out using a purposive sampling technique for five years, and produced 6 samples as observations. The results of the study indicate that individual corporate social responsibility (CSR) has a significant positive impact on financial performance. In contrast, company size and leverage individually have been shown to have a significant negative impact on financial performance. Meanwhile, simultaneously corporate social responsibility (CSR), company size, and leverage have a significant influence on financial performance.